PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN, KOMPETENSI SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOHI INFORMASI, DAN SISTEM PENGENDALIAN INTERN TERHADAP KUALITAS LAPORAN KEUANGAN SEKRETARIAT DAERAH KABUPATEN ENDE - Hermanus Reo (ITB AAS Indonesia Surakarta, 2024)
The purpose of this study was to determine the effect of the application of government accounting standards, human resource competencies, information technology utilization, and internal control system on the quality of financial reports of the Regional Secretariat of the Ende Regency. This research uses quantitave research. The population used in the study amounted to 156 respondents. The sample used in this study amounted to 42 respondents using a purposive sampling technique. The results of this study show that the variables of the application of government accounting standars, human resource competencies, information technology utilization, and internal control systems together have a significant impact on the quality of financial reports of the Regional Secretariat of Ende Regency by 64,1%. While the remaining 35,9% is explained by other variables outside the study.